(untitled) ("Journal "U". Economy. Management. Finance.", 2020)
The article presents various approaches to the definition of the term "startup" used in practice by Russian and American entrepreneurs, venture investors, technology brokers, managers of accelerators and business incubators. Comparative analysis and generalization of these approaches are carried out.